Assessing oral cancer awareness among undergraduate student in higher education institution using multiple linear regression / Norafefah Mohamad Sobri ... [et al.] - Mohamad Sobri, Norafefah; Ismail, Idari; Ismail, Nor Azima; Zulkfli, Siti Nurani; Anwar, Awanis; Ahmad, Noor Afifah; Wan Zulkifly, Wan Haszuliyanty Afieka (Unit Penerbitan UiTM Kelantan, 2021)
Oral cancer a highly morbid disease which has become a serious public health concern in most countries such as Germany, India and Indonesia and can cause death. Oral cancer is a disease that can occur in the surrounding of the mouth, oral cavity and oropharynx. The aim of this study was to identify the awareness of oral cancer among students in UiTM Kota Bharu, Kelantan. Four variables were investigated in the study including socio- demographic profile, knowledge of signs or symptoms of oral cancer, knowledge of risk factors of oral cancer and student's habits. Stratified Random Sampling was used to select the respondents. Pearson's correlation coefficient was used to analyze the signification relationship between dependent variable and independent variable. Multiple linear regression used to analyze the factors influence significantly to the awareness of oral cancer. Demographic analysis used to analyze the socio-demographic data. It was found that all three variables, (knowledge of signs or symptoms of oral cancer, knowledge of risk factors of oral cancer and habits) are significant effect to the awareness of oral cancer among students in UiTM Kota Bharu, Kelantan.